Species composition and distribution of marine macro algae at Co To and Thanh Lan archipelago - Tien, Dam Duc; Anh, Nguyen Thi Mai; Nguyen, Linh Manh; Hue, Pham Thu; Liao, Lawrence (Vietnam Journal of Marine Science and Technology, 2020)
This paper exhibites species composition and distribution of marine seaweed at 10 sites of Co To and Thanh Lan islands in May 2019. The studies record 76 species of marine algae in the area, belonging to four divisions: Cyanophytes, Rhodophytes, Ochrophytes and Chlorophytes. Among them, five species are classified into Cyanophytes (comprising 6.6% of total species); thirty-four species into Rhodophytes (44.7%); twenty-one species into Ochrophytes/Phaeophytes (27.6%) and sixteen species into Chlorophytes (21.1%). The species composition of marine seaweeds in Co To and Thanh Lan shows significant differences as follows: 22 species (sites number 4 and 10) to 58 species (site number 2) and the average value is 38.7 species per site. Sørensen similarity coefficient fluctuates from 0.33 (sites number 5 and 10) to 0.84 (sites number 1 and 3) and the average value is 0.53. The current investigations show that four species of twenty-one species are collected in the littoral zone and forty-two species in the sub-littoral zone (in which there are thirteen species distributed in both littoral zone and sub-littoral zone). The algal flora in Co To and Thanh Lan is characterized by subtropics.